Social Change in Gangetic Delta of India: a Participatory Rural Appraisal - Das, Samares Kumar; Tripathi, Hema (International Journal of Bio-resource and Stress Management, 2023)
Famous for the abode of notorious man-eating Royal Bengal Tiger Sundarban is largest delta and largest mangrove forest belt on earth. It is a UNESCO World Heritage Site. A participatory rural appraisal (PRA) was conducted (2003-04) in four purposively selected villages in Sundarban islands (Gangetic delta) of India to understand the social trend over a long period of time. PRA tools (oral history and time line) were applied to obtain information on various aspects of rural social life tracing back to the past. PRA reveals that rural people in Sundarban lived a tough life in recent past. Though a remarkable change in various aspects of village life has occurred in due course of time a lot has to be done to develop rural Sundarban compared with other developed regions of India. It was also observed that a little change has been brought by the programs planned and implemented by the government. It is recommended that before undertaking any program of promoted change perspectives of the villagers must be taken into consideration with an emphasis on environmental issues.